Surgical Treatment of Spine Deformations after Neonatal Sepsis (The Analysis of Clinical Series) - V. I. Zorin; D. G. Naumov; A. Yu. Mushkin; V. A. Evseev (Travmatologiâ i Ortopediâ Rossii, 2018)
Background. Neonatal sepsis presents one of the current issues in modern pediatrics. The orthopedic outcomes of such a state and the possibility of treatment, in particular by surgical spinal reconstruction, are rarely analyzed. Objective. To analyze pathology features and treatment outcomes in infants with vertebral complications resulted from neonatal sepsis.Material and Methods. The analysis of observation and treatment of 15 infants, who have undergone neonatal sepsis which led to vertebral lesion with subsequent gross kyphotic deformity formation, is presented.Results. Average age of infants was 2.5 months when spinal pathology was diagnosed. In 7 of the 15 observations, a local angular kyphosis was revealed when the acute phase of disease was already passed („cured“). The thoracic vertebrae were most often affected, mainly Th 7-8 vertebral bodies. Average kyphosis was 53°. All infants were operated on during the period from 2006 to 2017. Each had two-stage spinal reconstruction including the anterior spinal fusion using a titanium mesh cage filled with bone autografts, or an autogenous bone graft only. At the second stage, the instrumental correction and fixation of the spine with a multi-support laminar structure were performed. Average age of patients at the time of surgery was 14 months. Average value of kyphosis correction was 27°. Further correction and anterior spinal fusion were achieved when performing the incorporation of a titanium mesh cage with bone autografts. The histological and bacteriological examination of the surgical material did not reveal any signs of infection or inflammation. Correction of deformity and restoration of the supporting strength of anterior vertebral column as a result of surgery were achieved in all cases. Various complications in the early and late followup period were reported in a total of 7 cases. Repeated interventions were required in two patients: in one case in the early period (dislocation of the structure supporting hook) and in one case in the long-term period (graft resorption and kyphotic deformity relapse).Conclusion. One of the complications of neonatal sepsis is severe multilevel thoracic spondylitis, the outcome of which is the formation of severe kyphosis against the background of subtotal bone vertebral destruction. The principal possibility of radical spine reconstruction in infants with achievement of good anatomical and functional results is shown.